Addressing Solubility Limitations in Small-Molecule Ice Recrystallization Inhibitors and Evaluating their Use in Hematopoietic Stem Cell and Red Blood Cell Cryopreservation - Ampaw, Anna A. (Université d'Ottawa / University of Ottawa, 2022)
Cryopreservation is a method used to preserve the quality of various cell types over long periods of time (up to several years). Using this preservation method can vastly improve cellular therapies and regenerative medicine by allowing the creation of biobanks containing high-quality cell products. For example, biobanks of red blood cells (RBCs) would be beneficial for cellular therapies such as RBC transfusions, which are used to treat patients suffering from hemorrhages, anemias, and to replace blood loss after traumatic/surgical events. RBCs are currently preserved via hypothermic storage which limits their shelf life to 42 days. Similarly, biobanks of hematopoietic stem cells (HSCs) from umbilical cord blood would be beneficial for regenerative medicine therapies such as HSC transplantations, which offer treatment for blood- and immune-related diseases by reconstituting hematopoiesis. The outcome of these transplantations depends greatly on the quality of the cell product; therefore, it is important for preserved HSCs to have a minimum loss of viability and functionality. The cryopreservation of cells at low sub-zero temperatures (-80 to -196 degC) in a cryoprotectant solution allows for long-term storage. Common cryoprotectants used are 40% glycerol for the cryopreservation of RBCs and 10% dimethyl sulfoxide (DMSO) for the cryopreservation of HSCs. Before clinical use of cryopreserved products, DMSO and glycerol must be removed as they are severely toxic to patients upon infusion. The removal of 40% glycerol from RBCs is complicated, time consuming, and can result in a significant amount of cell damage. DMSO and glycerol also do not address the occurrence of ice recrystallization, which is the main cause of cellular damage during cryopreservation. Ice recrystallization describes the process of ice crystals growing larger and replacing smaller ice crystals, and significantly contributes to the damage of cells post-thaw. Therefore, methods to decrease the concentration of cryoprotectants to improve their removal process while also mitigating ice recrystallization is of interest. In nature, antifreeze proteins and glycoproteins (AF(G)Ps) are found in animals that can survive below-freezing temperatures. The Ben laboratory has used the structural components of AF(G)Ps to design several small-molecule carbohydrates that exhibit ice recrystallization (IRI) activity. O-aryl-b-D-glucosides and N-aryl-D-gluconamides are two classes of IRIs developed that have been used as supplemental additives to DMSO and glycerol to improve the post-thaw viabilities and functionalities of RBCs and HSCs. While many structure-activity relationship studies have been performed amongst these classes, one area of improvement is their solubilities to facilitate their use as cryoprotectants. This thesis focuses on the design of a new class of effective IRIs that have high solubilities (>100 mM in phosphate-buffered saline). Previous studies on the structure of small-molecule IRIs have demonstrated the importance of balancing the hydrophobicity and hydrophilicity within a molecule, making it difficult to achieve high solubilities. This thesis further explores this point by the design and synthesis of IRIs with polar functional groups possessing an overall molecular charge. N-aryl-D-gluconamides bearing amino- and azido-substituents were designed, however their synthesis was unsuccessful. Instead, this work revealed a synthetically facile route towards N-xylo-L-furanosyl amide and ester compounds. Phosphonate-substituted carbohydrates were also designed and synthesized as a means to obtain highly soluble IRIs. All of these compounds displayed high solubilities, however the majority of the compounds exhibited moderate IRI activities. While there are many assays used to measure IRI activity, this thesis also evaluates two of the most common IRI assays and their effect on IRI activity. In addition, the effect that cryoprotective agents (CPAs) like DMSO and glycerol have on IRI activity was also evaluated. In both cases, the type of assay used and the addition of CPAs affected the quantitative values describing IRI activity. Notably, DMSO and glycerol, had an antagonistic effect on the IRI activity of N-aryl-D-gluconamides and antifreeze protein type I. This was a significant observation since these IRIs are sufficient cryoprotectants in the presence of DMSO or glycerol. Lastly in this thesis, phosphonate-substituted IRIs and antifreeze (glyco)proteins (AF(G)Ps) were evaluated as cryoprotectants for the cryopreservation of RBCs and/or HSCs. These studies showed that phosphonate IRIs and AF(G)Ps were not toxic to RBCs and/or HSCs, however the concentrations evaluated were unable to improve the post-thaw viability and/or functionality of these cell types.
Keywords: cryopreservation; carbohydrate chemistry; organic chemistry; red blood cells